Transcriptomic profiling of sorghum leaves and roots responsive to drought stress at the seedling stage - Deng-feng ZHANG; Ting-ru ZENG; Xu-yang LIU; Chen-xi GAO; Yong-xiang LI; Chun-hui LI; Yan-chun SONG; Yun-su SHI; Tian-yu WANG; Yu LI (Journal of Integrative Agriculture, 2019)
Drought stress affects the growth and productivity of crop plants including sorghum. To study the molecular basis of drought tolerance in sorghum, we conducted the transcriptomic profiling of sorghum leaves and roots under drought stress using RNA-Seq method. A total of 510, 559, and 3 687 differentially expressed genes (DEGs) in leaves, 3 368, 5 093, and 4 635 DEGs in roots responding to mild drought, severe drought, and re-watering treatments were identified, respectively. Among them, 190 common DEGs in leaves and 1 644 common DEGs in roots were responsive to mild drought, severe drought, and re-watering environment. Gene Ontology (GO) enrichment analysis revealed that the GO categories related to drought tolerance include terms related to response to stimulus especially response to water deprivation, abscisic acid stimulus, and reactive oxygen species. The major transcription factor genes responsive to drought stress include heat stress transcription factor (HSF), ethylene-responsive transcription factor (ERF), Petunia NAM, Arabidopsis ATAF1/2 and CUC2 (NAC), WRKY transcription factor (WRKY), homeodomain leucine zipper transcription factor (HD-ZIP), basic helix-loop-helix transcription factor (bHLH), and V-myb myeloblastosis viral oncogene homolog transcription facotr (MYB). Functional protein genes for heat shock protein (HSPs), late-embryogenesis-abundant protein (LEAs), chaperones, aquaporins, and expansins might play important roles in sorghum drought tolerance. Moreover, the genomic regions enriched with HSP, expansin, and aquaporin genes responsive to drought stress could be used as powerful targets for improvement of drought tolerance in sorghum and other cereals. Overall, our results provide a genome-wide analysis of DEGs in sorghum leaves and roots under mild drought, severe drought, and re-watering environments. This study contributes to a better understanding of the molecular basis of drought tolerance of sorghum and can be useful for crop improvement.